Familism Scale: Confirmatory Factor Analysis in a Sample of Caregivers of Older Adults - Deusivania Vieira da Silva Falcão; Daniel Paulson; Manuel Herrera Legon; Carolina Irurita-Ballesteros (Paidéia (Ribeirão Preto), 2019)
Abstract The objective of this study was to translate and confirm the factor structure of the Familism Scale in the Brazilian Portuguese version. The sample included 716 Brazilian caregivers providing care to their own aging parents with Alzheimer’s Disease. The measures included the Familism Scale, the Filial Obligation Scale, the Life Satisfaction scale and the Center for Epidemiological Studies-Depression scale (CES-D). The questionnaire was individually filled online with use of the survey software package Qualtrics. Confirmatory Factor Analysis was used to examine the factor structure. The modified model demonstrated adequate fit (RMSEA = .063, CFI = .912). The hypotheses concerning convergence and divergence of validity from relevant variables were corroborated. These results support the use of the modified Familism Scale including twelve items and two factors with acceptable psychometric properties in a sample of Brazilian caregivers with Alzheimer’s Disease.